Techno-economic assessment of wet and dry torrefaction of biomass feedstock. (15th September 2020) - Akbari, Maryam; Oyedun, Adetoyese Olajire; Kumar, Amit
Abstract: Biomass can be converted to coal-like products known as hydrochar or biochar. Raw biomass generally has high moisture content. Wet torrefaction has gained considerable interest recently because of the unique characteristics of processing high-moisture content to a solid coal-like product. Five biomass feedstocks – wheat straw, pine, grape pomace, animal manure, and algae – were analyzed. The characteristics, as well as mass and energy yields of hydrochars and biochars from these feedstocks, were compared. Process simulation models were developed for both processes for each feedstock and techno-economic assessments conducted. The results indicate that hydrochars have superior characteristics, more coal-like properties, lower yields, and a higher cost of production (COP) than biochars for all cases except the pathways using manure as feedstock, where hydrochar COP is lower. The lowest production costs (without carbon credit) can be achieved through dry and wet torrefaction of grape pomace at 2.29 $/GJ and 4.14 $/GJ, respectively. Sensitivity and uncertainty analyses were also conducted for all pathways to understand the effects on production cost of varying different technical and economic factors. The results of this study will provide valuable insights into coal alternative products, especially in jurisdictions (like Alberta, Canada) planning to phase out coal plants. Highlights: Biocoal production via wet (WT) and dry (DT) torrefaction processes is investigated. Five feedstocks (wheat straw, pine, grape pomace, manure, and algae) are studied. Mass and energy yields and production costs (w and w/o carbon credit) are assessed. Cost of biocoal production (COP) is competitive with coal price in some pathways. Grape pomace has the lowest COP at 2.30 $/GJ and 4.15 $/GJ for DT and WT processes, respectively.